PENERAPAN METODE MUMTAZAH AL UMM WAL AB DALAM PEMBELAJARAN BAHASA ARAB DI PESANTREN ASSHIDDIQIYAH JAKARTA - Siti Rozinah; Dede Setiawan; Hayaturrohman Hayaturrohman; Muktar Sauri (Mozaic : Islam Nusantara, 2019)
The aims of this research implementation the the mumtazah method of al umm wal ab Arabic learning Pondok Pesantren Asshiddiqiyah Jakarta. The methode of research is qualitative research. The subject of research is the student of ulya madrasah diniyah takiyah ma 'hadul aytam Asshiddiqiyah. The result of this research is the application of the mumtazah method al umm wal ab madrasah diniyah takiyah ma 'hadul aytam asshiddiqiyah Uses 7 strategy, which area sentence, jumlah, Khabar, shilah, shifat, terms and answers. the problem with this method is every student has a different competition in the learning